Effectiveness Analysis of Crystalloids and Crystalloid-Colloid Combinations in Hospitalized Dengue Fever Patients Without Shock at RSUD Tangerang City - Helmawati Helmawati; Arrozi Arrozi; Duta Liana (Lembaga Pengembangan Kinerja Dosen, 2026)
The high cost of colloid fluids and the large number of patients are concerns in determining which treatment standard should be chosen from several treatment alternative, where the total cost for 43 cases with a combination of crystalloid colloid fluids is IDR 209.370.993 while the total cost for 45 cases of crystalloid fluids is only UDR 146.492.268 which causes hospital losses. This study aims to determine the difference in the cost-effectiveness between crystalloid fluids and crystalloid-colloid combinations in hospitalized dengue fever patients without shock at Tangerang City Hospital. The research design used was cross-sectional with a comparative quantitative analysis method, where cost effectiveness was analyzed using the Average Cost Effectiveness Ratios (ACER) method. There were two groups of study samples: the first group, 25 patients who received crystalloid fluids, and the second group, 23 patients who received crystalloid-colloid combination fluids. This study showed a difference in the average hospitalization costs for dengue patients between crystalloid fluid therapy and crystalloid-colloid combination therapy. Hospitalization costs for dengue patients were lower in the crystalloid fluid group, with a significant difference (p=0.000). It was also found that crystalloid fluids were more cost-effective than the crystalloid-colloid combination. The implications of the study results consist of theoretical implications and practical implications. Based on the results of the analysis carried out, the crystalloid solutions are more cost-effective than crystalloid-colloid combinations. This finding can be used as a consideration in making decisions and policies that are in accordance with quality control and cost control for patients covered by the National Health Insurance (BPJS Health insurance).